Establishing an interconnection between the technical and technological parameters of milking equipment based on the movement of a milk-air mixture in a milking machine - Aliiev, Elchyn; Paliy, Andriy; Dudin, Volodymyr; Kis, Viktor; Paliy, Anatoliy; Ostapenko, Volodymyr; Levchenko, Iruna; Prihodko, Mikola; Korg, Olga; Kladnytska, Larysa (Eastern-European Journal of Enterprise Technologies, 2022)
Machine milking is one of the main technological processes in the dairy industry whose efficiency level largely affects cattle breeding in general. The key role, in this case, belongs to milking equipment. The design and use of technical means of milking are associated with certain difficulties related to the imperfection of milk discharge. Therefore, the current study is due to the need to investigate the process of moving the milk mixture in a milking machine. A physical-mathematical model of the process of moving the two-phase milk-air mixture along the milk-conducting line of a milking machine has been built. The mathematical model relates the value of the fluctuating of vacuummetric pressure ΔP, the rate of milk discharge QM, the pulse rate ζ, and the value of working vacuummetric pressure P. It was found that in the milk-conducting system with the upper milk pipeline there is a large fluctuation of vacuummetric pressure ΔP=1.02–4.69 kPa, which exceeds the regulated value (2.5 kPa). In a milk-conducting system with a lower milk pipeline, the vacuummetric pressure fluctuation is ΔP=0.59–1.84 kPa. The patterns of change in the value of working pressure P and the frequency of pulsations ζ in the milking machines of simultaneous and pair action depending on the rate of milk discharge from the udder have been determined. It is established that the maximum deviation of the value of fluctuation of vacuummetric pressure ΔP between the experimental and theoretical data within a predefined range of factors is 0.81 kPa. The correlation coefficient is 0.92, which indicates the adequacy of the constructed models. Owing to this, the task of the rational choice of milking equipment is resolved